Editorial notes - Mohd. Israil, Khaliq Ahmad (World Academy of Islamic Management (WAIM), 2023)
Here is the great news of JIMS readers, contributors, editorial committee members. The JIMS is now indexed in MyJournal by the Malaysian government agency under the ministry of Higher Education. Kindly browse <https://myjurnal.mohe.gov.my/public/browse-journalview.php?id=1139> and enjoy reading this latest issue. This is another milestone achievement in the history of Journal of Islamic Management Studies to be published as an indexed journal. Beside this achievement the present issue of JIMS consists of five articles, as these contributions are made by established authors. This volume 6 issue 2 of the year 2023 of the Journal of Islamic Management Studies endeavours to add quality papers by academics from countries ranging from Indonesia, Bangladesh, and Malaysia. All the five papers expand the frontier of knowledge and intellectual insights by offering advancements and solutions to the contemporary challenges faced by either in banking and financing industry, marketing and consumers affairs and halal industry management issues in handling them from the Islamic perspectives. Among the five contributions, the article entitled, ‘the Global Islamic Banking: Expanding the Frontiers of Islamic Finance’ discusses issue related to the growth and prospects of Islamic banking globally. This article by the authors presents the study of global Islamic banking with the objectives to explore the insight of Islamic banking concepts and principles. It facilitates the understanding of the modus operandi of Islamic banking. The paper subsequently evaluated the recent development of Islamic banking globally across five main continents. A qualitative case study was used for this research to evaluate Islamic banking systems across continents.